Global evidence on nature-positive agricultural practices and their socio-economic and ecological impacts: a systematic review - Amoah, Joseph; Ngmensoa, Gregory; Annan, Reginald Adjetey (Frontiers in Sustainable Food Systems, 2025)
BackgroundNature Positive Food Production (NPFP) is an emerging framework for linking agricultural productivity with the regeneration of ecosystems. It works toward the restoration of soil health, improvement in biodiversity, and strengthening climate resilience of global food systems. Yet, evidence regarding how NPFP practices perform under a wide range of ecological and socio-economic contexts remains fragmented.MethodologyThis review synthesizes the evidence of nature-positive agricultural practices globally through a PRISMA framing. Searches in Scopus, Web of Science, PubMed, ScienceDirect, and Google Scholar include policy and grey literature relevant to the review published between 2010 and 2025. Eligible studies assessed agricultural approaches that presented quantifiable ecological restoration or sustainability outcomes. Of these, 45 studies were included and assessed for methodological quality using the adapted MMAT.ResultsVariations in the ecological and economic benefits exist for different types of farming, including regenerative agriculture, agroecology, agroforestry, climate-smart agriculture, and integrated pest management. This ranges from 15 to 30% increases in soil organic carbon, 20–50% improvements in on-farm biodiversity, and 10–25% improved yield stability relative to conventional approaches. Policies that promote coherence, agricultural investments, and inclusive financing channels have been widely recognized to enable scaling up nature-positive changes, especially in low- and middle-income countries.ConclusionNature-positive food production is the science-based pathway to bring ecosystems back to life in a way that secures safe, healthy, and sustainable food supplies. If this approach is to be scaled up globally, then good governance, fair finance, and knowledge platforms will be required that connect ecological regeneration with productivity and resilience.